Modern approaches to endovascular treatment of uterine leiomyoma - L.S.Kokov; M.M.Damirov; G.E. Belozerov; O.N.Oleynikova (IP Berlin A.V., 2018)
Individual features of the blood supply to the uterus and ovaries in 20-25% of cases cause failures in endovascular treatment of patients with uterine leiomyoma (ULM) and are forced to return to traditional surgical methods. The purpose of the study is to assess the possibilities of preventing iatrogenic complications of endovascular treatment of ULM through the use of separating occlusion of the uterine arteries, taking into account the characteristics of the blood supply to the uterus and ovaries. Materials and methods. The work is based on the analysis of the results. X-ray endovascular occlusion of the uterine arteries for ULM performed in 88 women aged 34-46 years (mean age 38.8 ± 2.5 years). The patients were divided into 2 groups: the 1st group comprised 65 patients without visible uterine-ovarian interarterial anastomoses. They performed standard embolization of the uterine arteries (EUA) using spherical PVA microemboli (COOK, USA), Embosphere (Merit Medical, USA) with a diameter of 500-700 microns. The second group consisted of 23 patients in whom utero-ovarian inter-arterial anastomoses were detected. In patients of this group, EUAs were produced with Embox cylindrical emboli (Plastis-M, Russia) with a length of 10 mm and a diameter of 500-700 μm, which occlude only the bed of the uterine arteries and are not capable of to overcome utero-ovarian inter-arterial anastomoses. In the 2nd group of EUA patients wore the character of occlusion, separating the uterine and ovarian arteries. The original EUA protocol was applied, which includes, in addition to the standard stages of selective arteriography of the uterine arteries, performing preliminary abdominal aortography to visualize the ovarian arteries and pelvic arteriography to assess pelvic vascular anatomy and identify utero-ovarian interarterial anastomoses. The results of the study. A total angiographic examination of the ovarian and uterine arteries, including a review angiography of the infrarenal section and bifurcation of the aorta, ileal vessels. In 23 (26.1%) patients with angiographic examination, uterine-ovarian arterio-arterial anastomoses. In 13 patients (56.5% of the detected anastomoses), these were type 1 anastomoses. In 10 patients (43.5% of the detected anastomoses), type 3 anastomoses were detected. Endovascular occlusion of the uterine arteries was performed in all patients. In 5 (7.69%) patients from the 1st group after EUA, amenorrhea occurred. In contrast, in all 23 patients from the 2nd group in the postembolization period, no observation of ovarian function was observed in any of the observations. Conclusion. For endovascular treatment of ULM in the presence of pronounced utero-ovarian interarterial anastomoses, the method of separating uterine artery occlusion is a safe and effective way to prevent ischemic damage to the ovaries.